2016
DOI: 10.1016/j.watres.2016.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Using Bayesian hierarchical models to better understand nitrate sources and sinks in agricultural watersheds

Abstract: Export coefficient models (ECMs) are often used to predict nutrient sources and sinks in watersheds because ECMs can flexibly incorporate processes and have minimal data requirements. However, ECMs do not quantify uncertainties in model structure, parameters, or predictions; nor do they account for spatial and temporal variability in land characteristics, weather, and management practices. We applied Bayesian hierarchical methods to address these problems in ECMs used to predict nitrate concentration in stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…While these approaches indicated the importance of hydroclimatology for driving interannual variability, they did not explicitly model the effects of hydroclimatological variables on source export rates or other watershed processes. Xia et al () considered land use change and four different statistical approaches for representing the interannual variability in watershed nitrate loading within a hybrid watershed model but did not model the effects of hydroclimatological variables on source export rates. In general, both of these previous studies suggested that dynamic parameter estimation was effective for simulating temporal variability in instream nutrient loads.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While these approaches indicated the importance of hydroclimatology for driving interannual variability, they did not explicitly model the effects of hydroclimatological variables on source export rates or other watershed processes. Xia et al () considered land use change and four different statistical approaches for representing the interannual variability in watershed nitrate loading within a hybrid watershed model but did not model the effects of hydroclimatological variables on source export rates. In general, both of these previous studies suggested that dynamic parameter estimation was effective for simulating temporal variability in instream nutrient loads.…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic parameter estimation allows model coefficients to vary over time in order to increase overall model fit (Congdon, ). In these studies, dynamic coefficients are compared to hydrometeorological variables through post hoc analyses (Wellen et al, ; Xia et al, ), rather than being directly integrated into the deterministic form of the model, as in our study (equation ). While both approaches have merit, directly integrating changes in both precipitation and source distributions into the hybrid model allows us to assess how these factors interact to influence nutrient loading and provides a framework for probabilistically evaluating different climate and land use scenarios.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations